The Study of Carbon Recovery from Electrolysis Aluminum Carbon Dust by Froth Flotation - Hesong Li; Jiaoru Wang; Wenyuan Hou; Mao Li; Benjun Cheng; Yuan Feng; Tibo Xu (Metals, 2021)
A large amount of carbon dust is generated in the process of aluminum smelting by molten salt electrolysis. The carbon dust is solid hazardous waste but contains a large quantity of recyclable components such as carbon and fluoride. How to recycle carbon dust more effectively is a challenge in the aluminum electrolysis field. In this study, X-ray diffraction, scanning electron microscope, and other methods were used to analyze the phase composition of electrolytic aluminum carbon dust. The effects of particle size distribution of carbon dust, impeller speed, reagent addition, mixing time, and flotation time on the flotation recovery of carbon dust were studied. The optimal flotation conditions were obtained and the flotation products were analyzed. The results show that the optimal particle size distribution is 70% of particles below 200 mesh, corresponding to a grinding time of 11 min. The optimum speed of the flotation machine was to be between 1600 and 1800 r/min with the best slurry concentration of 20–30% and 5 min mixing time, and the collector kerosene was suitable for adding in batches. Under the above conditions, the recovered carbon powder with a carbon content of 75.6% was obtained, and the carbon recovery rate was 86.9%.